The world economy and the Euro Area: Despite risks, global recovery is stabilizing - Ferdinand Fichtner; Guido Baldi; Christian Dreger; Hella Engerer; Stefan Gebauer; Malte Rieth (DIW Economic Bulletin, 2017)
Global economic output is expected to grow by 3.7 percent this year, and with a slightly stronger dynamic in the coming year; both predictions match the figures proposed in DIW Berlin's spring forecast, even though the year started off somewhat weaker than expected. But overall, economic recovery continues. Despite rising inflation rates, private consumption remains one of the main drivers in the developed countries, primarily due to the fact that more and more people are getting jobs. In the U.S. and Europe, corporate investment activity is once again picking up momentum. But although the elections in France and the Netherlands yielded positive outcomes with regard to the cohesion of the EU, and thus helped reduce the widespread unease, there remain risks for the global economy: the Brexit negotiations and the uncertainty surrounding the possible new elections in Italy are curbing the spending of both companies and consumers alike. Moreover, the emerging countries could be affected by capital outflows resulting from the U.S. Federal Reserve's interest rate hikes.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook